Design and performance analysis of a circular-arc gear pump operating at high pressure and high speed. (February 2016) - Zhou, Yang; Hao, Shuanghui; Hao, Minghui
This paper presents a high-pressure and high-speed gear pump for aerospace application and introduces a circular-arc tooth profile that has no trapping feature and whose gears are in continuous one-point contact in the plane of rotation. Basic dimensions are determined and performance parameters of the gear pump are obtained by structural design of the gear pump. The performance parameters are discussed for different tooth profiles. A disc tool and hob are designed to generate the circular-arc tooth profile. A computer-aided design (CAD) system for the design of the circular-arc gear pump is developed with features of tooth profile design, tool design, and numerical control. The test gears were processed to verify the correctness of CAD system. A study of the outlet pressure of the circular-arc gear pump reveals that the developed high-pressure and high-speed gear pump has low outlet pressure fluctuations.